2022
DOI: 10.3390/ijms232113131
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a Z-Type g-C3N4/(A-R)TiO2 Composite Catalyst and Its Mechanism for Degradation of Gaseous and Liquid Ammonia

Abstract: In this study, an (A-R)TiO2 catalyst (ART) was prepared via the sol–gel method, and g-C3N4 (CN) was used as an amendment to prepare the g-C3N4/(A-R)TiO2 composite catalyst (ARTCN). X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), Raman spectroscopy, N2 adsorption–desorption curves (BET), UV–vis diffuse absorption spectroscopy (UV–vis DRS), and fluorescence spectroscopy (PL) were used to evaluate the structure, morphology, specific surface area, optical proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The g-C 3 N 4 /(A-R)TiO 2 composite catalyst had a better dispersion, a smaller band gap width, a larger specific surface area, a stronger light absorption capacity, and a stronger photogenerated carrier separation ability than (A-R)TiO 2 catalyst [16]. Gaseous and liquid ammonia were used as the target pollutants to investigate the activity of the prepared catalysts, and the results showed that the air wetness and initial concentration of ammonia had a great influence on its degradation [16]. The superoxide anion radical (O 2 − ) and hydroxyl radical (OH) were the main active components in the photocatalytic reaction process [16].…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…The g-C 3 N 4 /(A-R)TiO 2 composite catalyst had a better dispersion, a smaller band gap width, a larger specific surface area, a stronger light absorption capacity, and a stronger photogenerated carrier separation ability than (A-R)TiO 2 catalyst [16]. Gaseous and liquid ammonia were used as the target pollutants to investigate the activity of the prepared catalysts, and the results showed that the air wetness and initial concentration of ammonia had a great influence on its degradation [16]. The superoxide anion radical (O 2 − ) and hydroxyl radical (OH) were the main active components in the photocatalytic reaction process [16].…”
mentioning
confidence: 99%
“…The study of Zhu et al [16] on the preparation of a Z-type g-C 3 N 4 /(A-R)TiO 2 composite catalyst and its mechanism for the degradation of gaseous and liquid ammonia is also presented in this Special Issue. The g-C 3 N 4 /(A-R)TiO 2 composite catalyst had a better dispersion, a smaller band gap width, a larger specific surface area, a stronger light absorption capacity, and a stronger photogenerated carrier separation ability than (A-R)TiO 2 catalyst [16].…”
mentioning
confidence: 99%
See 2 more Smart Citations